Predicting hydration and moisturizer ingredient effects on mechanical behavior of human stratum corneum. (July 2021) - Berkey, Christopher; Biniek, Krysta; Dauskardt, Reinhold H.
Abstract: Hydration of the outermost layer of human skin, the stratum corneum (SC), affects barrier function, physical appearance, and sensory perception of skin. Water loss, ubiquitously associated with dry skin conditions, results in the development of mechanical tensile stresses that lead to the perception of skin tightness and provide a driving force for damage in the form of chapping or cracking. Restorative moisturizing formulations contain molecular components that counteract the effects of water loss. However, the quantitative connection between water loss and SC mechanical behavior together with a predictive model has remained elusive. We develop a diffusional-based mechanics model that accurately predicts the SC mechanical behavior during hydration or dehydration over a wide range of ambient humidity conditions and presence of moisturizing ingredients. The model was validated with published studies including SC water diffusion, quantitative Raman spectroscopy, and mechanical property and stress characterization. The roles of mobile and partially bound water states are included together with one humectant and three cosmetic emollient molecules commonly used in moisturizing formulations. The model accurately predicts the effects of moisture content and moisturizer ingredients on SC mechanical behavior and provides a quantitative predictive capability that can be employed in the design of efficacious treatments.